Pengembangan Media Puzzle Bangun Datar Untuk Meningkatkan Pemahaman Konsep Materi Bangun Datar Siswa Kelas II Sekolah Dasar - RAHAYU, RISKA; ARDHI SAPUTRO, BAGUS; FITA ASRI UNTARI, MEI (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low conceptual understanding in geometry, particularly in recognizing and classifying two-dimensional shapes, remains a challenge for many elementary school students. Traditional instructional methods often lack interactive elements that stimulate active learning, thereby limiting students’ engagement and retention. This study aims to develop and validate a two-dimensional shape puzzle learning media as an innovative approach to strengthen concept mastery. Using the ADDIE development model comprising analysis, design, development, implementation, and evaluation the research involved a purposive sample of 30 second-grade students from SD Negeri 07 Purwoharjo. Data were collected through expert validation sheets, student response questionnaires, and learning achievement tests. Validation results from material and media experts indicated a “very feasible” category, with high scores in both content accuracy and visual appeal. Classroom implementation demonstrated a significant improvement in students’ understanding, reflected in higher post-test scores compared to pre-test results, and N-Gain values ranging from medium to high. These findings highlight the effectiveness of puzzle-based learning media in fostering engagement, supporting active exploration, and enhancing conceptual comprehension in elementary geometry education.